Magnetic levitation in orbitron system - Zub, S.S. (Вопросы атомной науки и техники, 2014)
This paper devoted to proof the existence of stable quasi-periodic motions of the magnetic dipole that is under the action of the external magnetic field and homogeneous field of gravity. For proof we used energy-momentum method that is the group-theoretic method of Hamiltonian mechanics. Numerical simulation shows the possibility of realization of stable motions with physically reasonable parameters of the system.